2018
DOI: 10.1002/jbmr.3393
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Material Properties and Structure to Increased Bone Fragility for a Given Bone Mass in the UCD-T2DM Rat Model of Type 2 Diabetes

Abstract: Adults with type 2 diabetes (T2D) have a higher fracture risk for a given bone quantity, but the mechanisms remain unclear. Using a rat model of polygenic obese T2D, we demonstrate that diabetes significantly reduces whole-bone strength for a given bone mass (μCT-derived BMC), and we quantify the roles of T2D-induced deficits in material properties versus bone structure; ie, geometry and microarchitecture. Lumbar vertebrae and ulnae were harvested from 6-month-old lean Sprague-Dawley rats, obese Sprague-Dawley… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 54 publications
(76 reference statements)
4
49
1
Order By: Relevance
“…1,2 Recent studies focused on bone structure quality have shown that trabecular and cortical bone microstructure are more fragile in patients with T2DM. [3][4][5][6] These findings have led to increased interest in the mechanisms of T2DM-induced bone microstructure damage, with the goal of developing new treatments for T2DM-induced osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Recent studies focused on bone structure quality have shown that trabecular and cortical bone microstructure are more fragile in patients with T2DM. [3][4][5][6] These findings have led to increased interest in the mechanisms of T2DM-induced bone microstructure damage, with the goal of developing new treatments for T2DM-induced osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Bone damping is a property of bone protein, and the elevated fracture risk in patients with Type 2 diabetes is attributed to the decoration of collagen with advanced glycation end products (AGEs) [37]. In our study of cadaveric arms, CBMT measurements of ulna damping were 25% lower in ulnas of nine donors with Type 2 diabetes than in ulnas of the same size in arms of donors without diabetes (p = 0.03).…”
Section: Dynamic Mechanical Loadingmentioning
confidence: 64%
“…These results illustrate that AGEs alter bone such that they require less force to initiate a crack and are less resistant to the initiation of a fracture. Specifically, accumulation of AGEs that form within and between collagen fibers can stiffen the collagen matrix, which, in turn, can result in delamination of the interfaces between collagen and mineral to reduce bone's fracture toughness . Our findings confirm results from a study that determined by finite element analyses that AGEs decrease bone's crack initiation toughness .…”
Section: Discussionmentioning
confidence: 99%